2018
DOI: 10.3390/polym10060658
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Aging Behavior of Natural Rubber/Butadiene Rubber (NR/BR) Blends Using a Parallel Spring Model

Abstract: Natural rubber/butadiene rubber (NR/BR) blends are widely used in industrial areas for absorbing vibrations and shocks because of their excellent elastic stability. However, when an industrial-equipment surface is exposed to sunlight and oxygen over a long period of time, the rubber hardens. As a result, the tensile properties of the rubber material and the behavior of the strain-energy density function are changed, greatly reducing the performance of the rubber product. However, only a few experimental studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…These authors also verified that the emulsion-polymerized ABS showed better thermal stability, and associated these results with the presence of a cross-linked network in the PB fraction, which is expected to promote a reduction in the free volume and oxygen diffusion [22,23]. Such PB crosslinking also occurs during aging and processing forming gels; however, the addition of AOs can improve the stability, reducing crosslinking [14,24].…”
Section: Introductionmentioning
confidence: 86%
“…These authors also verified that the emulsion-polymerized ABS showed better thermal stability, and associated these results with the presence of a cross-linked network in the PB fraction, which is expected to promote a reduction in the free volume and oxygen diffusion [22,23]. Such PB crosslinking also occurs during aging and processing forming gels; however, the addition of AOs can improve the stability, reducing crosslinking [14,24].…”
Section: Introductionmentioning
confidence: 86%
“…For composites with one matrix system, only the calculated interaction parameter (χ 1 ) of that matrix is used in the estimation of its crosslinking density (N) [28,29]. Researchers have adopted the use of the mixtures rule [30] for blend systems or a method of averaging χ 1 for each the polymer involved to compute the N of composites with many matrix phases [18,20,31]. In this present study, we also adopted the latter method of averaging χ 1 for the blend systems, for the computation of their respective N values.…”
Section: Crosslinking Density the Degree Of Swelling Of Polymer Compmentioning
confidence: 99%
“…where β 1 is the lattice constant, usually 0.34, δ r is the solubility parameter of NR (8.12 [cal/cm 3 ] 1/2 ), and δ s is the solubility parameter of toluene (8.97 [cal/cm 3 ] 1/2 ). [32][33][34] The tensile properties of DNR and WNR compounds were determined from their strain-stress curves recorded using a universal tensile tester (Daekyung Co., DUT-500C) at ambient temperature with a crosshead speed of 500 mm/min according to ASTM D 412. Four dumbbelltype samples were used for each measurement.…”
Section: Evaluation Of Dnr and Wnr Compoundsmentioning
confidence: 99%